Cancer cell death induced by ruthenium complexes - Žakula, Jelena; D. Nešić , Maja; Matijević, Milica; Stepić, Milutin; Petković, Marijana; Korićanac, Lela (Biologia Serbica, 2023)
Cancer is a complex and often fatal disease characterized by uncontrolled cell division. The most commonly used chemotherapeutics target rapidly dividing cancer cells but, at the same time, damage healthy dividing cells. New metal-based complexes, such as ruthenium complexes, that possess cytotoxic properties, have been developed to overcome these challenges. Ruthenium complexes achieve their antitumor effect mainly by inducing apoptosis. In recent years, induction of other types of cell death, such as ferroptosis and autophagy, was also reported. The dual role of autophagy in cancer cells is a major challenge for the application of metallocomplexes in cancer treatment, either as inducers or inhibitors of autophagy. Also, the effect of ruthenium complexes on other cellular processes such as cell cycle, cell migration, and adhesion are promising approaches in cancer treatment. Our results indicated a significant influence of Ru(II) complexes on these processes in melanoma, cervical and pancreatic cancer. The aim of this review is to summarize the latest data on the effect of ruthenium complexes on different types of cell death.